2010
DOI: 10.7202/045079ar
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Language Anxiety and Student Interpreters’ Learning Outcomes: Implications for the Theory and Measurement of Interpretation Learning Anxiety

Abstract: Although anxiety has been documented as an important variable in both interpretation performance and second language acquisition, there has been virtually no research on the interconnections between the anxiety reactions induced by these two cross-linguistic / cultural endeavors. A review of the literature on anxiety and interpretation performance finds that most of the existing studies have treated the anxiety induced by interpretation as a transfer of other general types of anxieties, such as trait a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 22 publications
1
27
0
15
Order By: Relevance
“…Nevertheless, two individual affective strategies (items 39 and 40) were significantly and positively associated with semester grades, suggesting that the strategies used by interpreting students to lower their foreign language anxiety and overcome their fear about making mistakes did have some bearing on their interpreting achievement. This result echoed both Chiang's (2010) finding that foreign language (English) anxiety had a negative correlation with Mandarin-English interpreting achievement and Bontempo and Napier's (2011) finding that emotional stability (anxiety and neuroticism) was a significant predictor of signed interpreters' self-rated interpreting competence. These results suggested that the ability to contain anxiety in general, and foreign language anxiety in particular, was a part of interpreting aptitude which could effectively discriminate between more and less successful interpreting students.…”
Section: Relationship Between English Learning Strategies and Interprsupporting
confidence: 66%
“…Nevertheless, two individual affective strategies (items 39 and 40) were significantly and positively associated with semester grades, suggesting that the strategies used by interpreting students to lower their foreign language anxiety and overcome their fear about making mistakes did have some bearing on their interpreting achievement. This result echoed both Chiang's (2010) finding that foreign language (English) anxiety had a negative correlation with Mandarin-English interpreting achievement and Bontempo and Napier's (2011) finding that emotional stability (anxiety and neuroticism) was a significant predictor of signed interpreters' self-rated interpreting competence. These results suggested that the ability to contain anxiety in general, and foreign language anxiety in particular, was a part of interpreting aptitude which could effectively discriminate between more and less successful interpreting students.…”
Section: Relationship Between English Learning Strategies and Interprsupporting
confidence: 66%
“…In survey research participants are asked to fill in a questionnaire in which they are asked about their current mental or emotional state. For details on the results of studies on self-reported stress/anxiety in interpreting, see : Cooper et al (1982), Jiménez Ivars and Pinazo Calatayud (2001), Chiang (2009), Chiang (2010 and Kao and Craigie (2013).…”
Section: Physiological Manifestation Of Stress In Conference Interprementioning
confidence: 99%
“…Interpreters' stress has been conceptualized as situation specific (Chiang, 2010). Most of those who have researched interpreters' stress have focused on the causes and seriousness of stress.…”
mentioning
confidence: 99%